1993
DOI: 10.1037/0022-0167.40.3.357
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing among antecedents, concomitants, and consequences of problem-solving appraisal and depressive symptoms.

Abstract: In the present study, a prospective design was used and data were collected from 277 introductory psychology students to distinguish among the antecedents, concomitants, and consequences of problem-solving appraisal and depression. The results of structural equation path analyses provide preliminary evidence that self-appraised ineffective problem-solving ability is an antecedent that may play a causal role in predicting future depressive symptoms. However, the results also suggest that problem-solving apprais… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 38 publications
3
43
0
1
Order By: Relevance
“…The finding that PSI scores of patients with avoidant, narcissistic, and borderline PDs were no longer significantly different from those of patients with no PD diagnosis after controlling for levels of baseline depression suggests that these patients' very poor problem-solving scores were related to the severity of their depressive symptoms. Taken alone, these results support the argument that poor perceived problem solving among patients with depression-with or without PDs-may represent a state-dependent phenomenon rather than a trait vulnerability [Dixon et al, 1993]. However, the PSI is a measure of problem-solving self-appraisal.…”
Section: Discussionsupporting
confidence: 49%
“…The finding that PSI scores of patients with avoidant, narcissistic, and borderline PDs were no longer significantly different from those of patients with no PD diagnosis after controlling for levels of baseline depression suggests that these patients' very poor problem-solving scores were related to the severity of their depressive symptoms. Taken alone, these results support the argument that poor perceived problem solving among patients with depression-with or without PDs-may represent a state-dependent phenomenon rather than a trait vulnerability [Dixon et al, 1993]. However, the PSI is a measure of problem-solving self-appraisal.…”
Section: Discussionsupporting
confidence: 49%
“…Problem solving appraisal was the unique significant predictor. Literature has already shown that problem solving may play a central role in adaptive responses evidenced in a large variety of stressful situations [48,24]. Additionally, research involving adults with vision loss has already suggested a possible role of problem solving in finding solutions and in adapting to difficulties they encounter in everyday life specifically due to vision loss [22,26,27,8].…”
Section: Discussionmentioning
confidence: 99%
“…PCS and MCS and mean score in the daily VFQ subscale (analyzing near vision, distance vision, social functioning, peripheral vision and color vision) were entered into the equation, respectively, as the first and second step; then, as a third step, the PSI total score was entered to highlight the incremental gain in the variance explained and the more crucial role of problem solving skills over health and functional consequences on well-being [22,24,25] and more particularly on satisfaction for QoL experienced. All variables were forced into the model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it might be useful to examine the validity of the factor structure of the PSI in a more collectivistic culture (e.g., Asian culture) and emic approaches in how people from different cultures solve problems in stressful situations. Likewise, it might be useful to test other models of problem solving, such as a reciprocal model that would also predict distress being associated with lower confidence and problem avoidance (see Dixon, Heppner, Burnett, Anderson, & Wood, 1993).…”
Section: Discussionmentioning
confidence: 99%